Wind energy potential assessment in Naxos Island, Greece - Fyrippis, Ioannis; Axaopoulos, Petros J.; Panayiotou, Gregoris (My University, 2010)
The current paper presents an investigation of the wind power potential of Koronos village, a remote location in the northeastern part of Naxos Island, Greece, using real wind data by a measurement mast. The obtained wind characteristics were statistically analysed using the Weibull and Rayleigh distribution functions. The results from this investigation showed that the selected site falls under Class 7 of the international system of wind classification as the mean annual wind speed recorded in the area was 7.4 m/s and the corresponding annual mean power density was estimated to be 420 W/m2. Furthermore, the prevailing wind directions characterising the area were the northeastern and the north–northeastern. From the statistical analysis of these results, it was revealed that the Weibull model fitted the actual data better. This remark was further enhanced by the evaluation of the performance of these two distributions
Keywords: Aegean Sea Greece; Distribution; Weibull-Rayleigh; Wind potential; Wind speed Wind power density